KAJIAN TINGKAT WALKABILITY JALUR PEJALAN KAKI DI KAWASAN CBD BINTARO JAYA, KOTA TANGERANG SELATAN - Wisnu Sasongko; Nadiva Azzahra Ramadhani; Eddi Basuki Kurniawan (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2022)
Walkability is carried out to measure the feasibility of the pedestrian path in the Bintaro Jaya CBD Area, South Tangerang City. According to the RTRW of South Tangerang City in 2011-2031, the Bintaro Jaya CBD area is a strategic area from the point of view of the importance of economic growth and in providing pedestrian paths, it considers aspects of safety, comfort, and security as well as taking into account pedestrian paths with special needs. In the existing condition, it has not been implemented according to the RTRW of South Tangerang City in 2011-2031, namely there are still infrastructure and facilities for pedestrian paths and pedestrian paths with special needs that are uneven, as well as side obstacles and damage to pedestrian paths. The aim of this study is to determine the level of walkability of pedestrian paths in the CBD area of Bintaro Jaya and the type of study is quantitative with the method of analyzing the level of walkability of pedestrian paths using 9 parameters based on Leather et all in 2011. The results of the walkability level analysis show that the lowest walkability score is in segment 3A with a value of 37.0 or not walkable and the highest walkability score is in segment 5A with a value of 74.2 or highly walkable, while the walkability score for one area is 51.7 or waiting to walk. Keywords: Pedestrian Paths, Walkability, Bintaro Jaya CBD Area.